Accounting of non-steady wing fairing and tail group during the analysis of influence of atmosphere turbulence at dynamic of aircraft flight - Антонова, А. О. (Proceedings of National Aviation University (archive), 1999)
Compared are the results of calculation of vertical transfer, number of crossing of zero level of transfer and moment delay of tail group as to the moment of aircraft wing under action of accidental wind gust provoked by atmosphere turbulence for different means of accounting of non- steady fairing. Proposed is the approximated formula for wing lift at sinusoidal wind gust